2018
DOI: 10.1292/jvms.18-0043
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic volume of recipient oocytes affects the nucleus reprogramming and the developmental competence of HMC buffalo (<i>Bubalus bubalis</i>) embryos

Abstract: The present study was undertaken to examine the effects of cytoplasmic volume on nucleus reprogramming and developmental competence of buffalo handmade cloning (HMC) embryos. We found that both HMC embryos derived from ~150% cytoplasm or ~225% cytoplasm resulted in a higher blastocyst rate and total cell number of blastocyst in comparison with those from ~75% cytoplasm (25.4 ± 2.0, 27.9 ± 1.6% vs. 17.9 ± 3.1%; 150 ± 10, 169 ± 12 vs. 85 ± 6, P<0.05). Meanwhile, the proportions of nuclear envelope breakdown (NEB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…This observation indicated the hypothesis that an affected reprogramming process or improper maternal-zygotic transition might be the consequence of an inappropriate cytoplast activation due to the lack of sperm contribution. Despite the cytoplasmic volume being important for the nucleus reprogramming and developmental competence of embryos [50], proper progress of the post-fertilization cytoplasmic event may also be crucial to support subsequent embryo development. However, further study is needed to clarify the mechanism responsible for the difference in cytoplasmic function among abnormally fertilized embryos and, thus, the biological marker indicating cytoplasmic function.…”
Section: Discussionmentioning
confidence: 99%
“…This observation indicated the hypothesis that an affected reprogramming process or improper maternal-zygotic transition might be the consequence of an inappropriate cytoplast activation due to the lack of sperm contribution. Despite the cytoplasmic volume being important for the nucleus reprogramming and developmental competence of embryos [50], proper progress of the post-fertilization cytoplasmic event may also be crucial to support subsequent embryo development. However, further study is needed to clarify the mechanism responsible for the difference in cytoplasmic function among abnormally fertilized embryos and, thus, the biological marker indicating cytoplasmic function.…”
Section: Discussionmentioning
confidence: 99%
“…The cloned embryo efficiency is related to gene expression, histone methylation, and acetylation. Moreover, cytoplasmic volume and donor cells positively affect embryonic development and nuclear reprogramming (Beyhan et al, 2007;Liu et al, 2018). In a previous study, the reconstructed cloned embryo, using CICT, showed that gene expression levels of DNMT 1 and DNMT 3a were significantly lower than in the traditional cloning method, indicating that CICT can improve epigenetic reprogramming.…”
Section: Figmentioning
confidence: 97%